2006
DOI: 10.1093/nar/gkl819
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid residue doublet propensity in the protein–RNA interface and its application to RNA interface prediction

Abstract: Protein–RNA interactions play essential roles in a number of regulatory mechanisms for gene expression such as RNA splicing, transport, translation and post-transcriptional control. As the number of available protein–RNA complex 3D structures has increased, it is now possible to statistically examine protein–RNA interactions based on 3D structures. We performed computational analyses of 86 representative protein–RNA complexes retrieved from the Protein Data Bank. Interface residue propensity, a measure of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(132 citation statements)
references
References 52 publications
2
125
2
Order By: Relevance
“…9,15,16 In practically all of the studies, the favored residues are R and K, but their pairwise preferences for the ribonucleotides change. In our work here and in others, 9,16 there are no significant differences on the preferences of R and K for any ribonucleotide, but in some studies they see preferred pairs as R-U, 11,12,15 or K-A. 11,12 Interestingly, in our study we can see H residues with higher pairwise propensities, while this is not observed in any of the previous studies.…”
Section: New Pairwise Propensities For Protein-rna Interaction Compacontrasting
confidence: 54%
See 2 more Smart Citations
“…9,15,16 In practically all of the studies, the favored residues are R and K, but their pairwise preferences for the ribonucleotides change. In our work here and in others, 9,16 there are no significant differences on the preferences of R and K for any ribonucleotide, but in some studies they see preferred pairs as R-U, 11,12,15 or K-A. 11,12 Interestingly, in our study we can see H residues with higher pairwise propensities, while this is not observed in any of the previous studies.…”
Section: New Pairwise Propensities For Protein-rna Interaction Compacontrasting
confidence: 54%
“…In our work here and in others, 9,16 there are no significant differences on the preferences of R and K for any ribonucleotide, but in some studies they see preferred pairs as R-U, 11,12,15 or K-A. 11,12 Interestingly, in our study we can see H residues with higher pairwise propensities, while this is not observed in any of the previous studies. Histidine residue can act as positively charged, depending on the environment, so this can explain its high propensities.…”
Section: New Pairwise Propensities For Protein-rna Interaction Compacontrasting
confidence: 54%
See 1 more Smart Citation
“…The partial sequence of human ORC1 from 1 to 530 was submitted to FUGUE server. Once the threedimensional structure was predicted, RNA-binding residues were further predicted using KYG method (21).…”
Section: Preparation Of Recombinant Human Orc-complementarymentioning
confidence: 99%
“…Residues critical for RNA/ssDNA binding within the domain were predicted using the KYG method (21). There are two candidate surfaces for RNA/ssDNA binding, one of which coincides with the S-adenosyl-L-homocysteine (SAH) binding site (Fig.…”
Section: The G-rich Rna/ssdna-binding Domain Resembles Part Ofmentioning
confidence: 99%